Past, current and future of legal regulation of drugs compounding in the Russian Federation - D. D. Mamedov; D. S. Yurochkin; Z. M. Golant; V. S. Fisenko; A. V. Alekhin; I. A. Narkevich (Фармация и фармакология (Пятигорск))
Today the activities of compounding pharmacies in terms of the drug compounding and in-pharmacy packaging of approval drugs is considered as a priority social task of the Russian Federation, due to the need to solve problems that are aimed at ensuring the strategic independence of the state from external and internal challenges, as well as threats, widespread introduction of personalized pharmacotherapy methods, opportunities in the field of optimizing the costs of the healthcare system.The aim of the study was to conduct a historical analysis and comprehensive review of the current state of legal and regulatory framework of the Russian pharmaceutical market in the field of compounding drugs, as well as to develop proposals for improving the regulatory field.Materials and methods. The following methodological tools – empirical, theoretical, quantitative ones – have been used in the work. In particular, an analysis of a wide range of relevant sources of information was carried out and information was obtained from legal and regulatory framework for the activities of compounding pharmacies in the Russian Federation, which was implemented using a bibliometric method of analysis.Results. The main elements of the Russian legislation in the field of drug circulation with the aim of a comprehensive understanding of the classification and determination of the role of extemporaneous drugs in the Russian healthcare system, are presented in the article. A historical and technical analysis of the regulatory practice development is consistently presented. The key issues of organizing the pharmaceutical business in the field of compounding and dispensing of drugs on the territory of the Russian Federation have been considered, and current problems that need to be solved when improving the regulatory field, are presented.Conclusion. The review conducted makes it possible to clarify further actions to improve federal legislation and delegated legislation in the field of circulation of compounded drugs by pharmacy organizations. The work presents recommendations that will contribute to the development of compounding pharmacies in the constituent entities of the Russian Federation.